Heterotopic Ossification of the Indirect Head of the Rectus Femoris - Rob Vernelen; Filip M. Vanhoenacker (Journal of the Belgian Society of Radiology)
Teaching point: The clues to the correct diagnosis of heterotopic ossification of the indirect head of the rectus femoris are its location above the acetabular rim and its (inverted) comma‑like morphology.